Site Test Performance and Numerical Study of Vertical Axis Hydrokinetic Turbine Straight Blade Cascaded (VAHT–SBC) - Ridho Hantoro; Sarwono Sarwono; Fernando Parsaulian Panjaitan; Erna Septyaningrum; Nuril Hidayati (Journal of Engineering and Technological Sciences, 2021)
The Vertical Axis Hydrokinetic Turbine â Straight Blade Cascaded (VAHT-SBC) is a type of energy generation technology developed to meet the increasing demand for renewable energy. Previous studies have been carried out to enhance the efficiency of the turbine through several aspects. To deploy a turbine on site, a study on its power generation and conversion is needed. In this research, the VAHTâSBC was integrated with a permanent magnet synchronous generator (PMSG) by a pulley and belt transmission system. This study was conducted by experimental and numerical analysis. The CFD simulation result showed that the highest torque of the turbine was found at 0° and 360°, with an average value of 23.923 Nm and with current velocity at 0.92 m/s. The experimental data showed that the voltage and frequency were proportional to the generator rotational speed and inversely correlated with the load given to the integration system. In the inverter, the voltage and frequency values were stable at 230 V and 56 Hz respectively. The VAHT-SBC prototype was able to produce a maximum power of 50 W on site, with a current velocity of 0.82 and 0.92 m/s.